MICROBIOLOGICAL CHARACTERISTICS AND PHYTOCHEMICAL SCREENING OF SOME HERBAL TEAS IN NIGERIA - Barry Aigbodion Omogbai; Marcel Ikenebomeh (European Scientific Journal, ESJ, 2013)
Aims: The present study was undertaken to investigate the bacterial and fungal contamination of herbal teas in the Nigerian market with special reference to Benin City.Methodology And Results: Twenty-six (26) samples of five different types of herbal teas: antidiarrhoeal, antimalarial, antiobesity (slimming), antihypertensive and antidiabetic teas were analysed using standard microbiological procedures. All samples of the herbal teas were contaminated with both bacteria and fungi. The bacteria count ranged from 1.1x101 to 4.8x102cfu/g. The fungal count ranged from 1.1x102 to 4.5x105cfu/g. Bacterial isolates from herbal teas include: Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis, Pseudomanas flourecens, Pseudomonas aeruginosa, Klebsiella pneumoniae, Serratia marcenscens, Salmonella typhimurium, and Escherichia coli. Fungal isolates were Aspergillus niger, Aspergillus flavus, Penicillium expansum, Rhizopus stolonifer and Fusarium solanii. Of all the bacterial isolates, Bacillus subtilis had the highest occurrence (100%) and the least was Salmonella typhimurium (3%). Among the fungi, Aspergillus niger had the highest occurrence (100%) and the least was Rhizopus stolonifer (10%). The bacteria isolates showed multiple resistace pattern to the antibiotics with all gram-negative exhibiting resistance to ampicillin. Phytochemical screening of the herbal teas revealed the presence of flavonoids, alkaloids, phenols, tannin and saponins.Conclusion, Significance And Impact Of Study: The presence of secondary metabolites justify the use of herbal teas.Good manufacturing practice and proper quality control is however needed for the continued use of the products to curtail antibiotic resistance.